Serine protease PRSS23 drives gastric cancer by enhancing tumor associated macrophage infiltration via FGF2 - Qin, Shanshan; Wang, Zidi; Huang, Congcong; Huang, Pan; Li, Dandan (Frontiers in Immunology, 2022)
Serine proteases has been considered to be closely associated with the inflammatory response and tumor progression. As a novel serine protease, the biological function of PRSS23 is rarely studied in cancers. In this study, the prognostic significance of PRSS23 was analyzed in two-independent gastric cancer (GC) cohorts. PRSS23 overexpression was clinically correlated with poor prognosis and macrophage infiltration of GC patients. Loss-of-function study verified that PRSS23 plays oncogenic role in GC. RNA-seq, qRT-PCR, western blotting and ELISA assay confirmed that serine protease PRSS23 positively regulated FGF2 expression and secretion. Single-cell analysis and gene expression correlation analysis showed that PRSS23 and FGF2 were high expressed in fibroblasts, and highly co-expressed with the biomarkers of tumor associated macrophages (TAMs), cancer-associated fibroblasts (CAFs) and mesenchymal cells. Functional analysis confirmed PRSS23/FGF2 was required for TAM infiltration. Rescue assay further verified that PRSS23 promotes GC progression and TAM infiltration through FGF2. Survival analysis showed that high infiltration of M1-macrophage predicted favorable prognosis, while high infiltration level of M2-macrophage predicted poor prognosis in GC. Our finding highlights that PRSS23 promotes TAM infiltration through regulating FGF2 expression and secretion, thereby resulting in a poor prognosis.